Exposure rate in mobile c-arm fluoroscopy and radioiodine therapy - Shalleh, Norzulaili Md (2004)
This study is done to measure the exposure rate from mobile c-arm fluoroscopy and patients undergo radioiodine therapy. The measurement of exposure rate from mobile c-arm fluoroscopy was carried out using survey meter model 451 B, and also lead apron with 0.5 mm lead equivalence thickness. The exposure time, distance, shielding material and value of kVp and mAs were considered. This study was done by varied the exposure time of mobile c-arm fluoroscopy while the value of kVp was remaining constant. This was done to see the effect of exposure time to the exposure rate. From this study, we found that the exposure rate was increased exponentially with exposure time. This study also done by varied the distance of survey meter from mobile c-arm fluoroscopy. This was done to see the effect of distance to the exposure rate. From this study, we found that the exposure rate decreased for about 30% when the distance increased by 1 0 em. Besides that, this study was also done; by covering the survey meter with lead apron with 0.5 mm lead equivalence thickness. This was done to see the effect of shielding to the exposure rate. We found that the exposure rate decreased for more than 90o/o when the lead apron was used. We also measured the exposure rate from patients undergo radioiodine therapy. This study was done after the patients had drunk the radioiodine solution for 30 minutes. This study also used survey meter model 451 B to measure the exposure rate from various distance. From this study, we found that the exposure rate from radioiodine therapy patients decreased exponentially with increasing distance. As conclusion, we can say that the exposure rate from mobile c-arm fluoroscopy and patients undergo radioiodine therapy, can be minimized by increasing distance, decreasing exposure time, and also by using shielding materials.